2003
DOI: 10.1074/jbc.m211824200
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Induced by Hyperosmotic Stress Mediates Cardiomyocyte Apoptosis

Abstract: Cells adapt to hyperosmotic conditions by several mechanisms, including accumulation of sorbitol via induction of the polyol pathway. Failure to adapt to osmotic stress can result in apoptotic cell death. In the present study, we assessed the role of aldose reductase, the key enzyme of the polyol pathway, in cardiac myocyte apoptosis. Hyperosmotic stress, elicited by exposure of cultured rat cardiac myocytes to the nonpermeant solutes sorbitol and mannitol, caused identical cell shrinkage and adaptive hexose u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 83 publications
7
68
0
1
Order By: Relevance
“…AKR1B1 is also known as the cause for cell apoptosis in somatic cells that accumulate sorbitol (Galvez et al 2003, Wirtu et al 2004. Expression of AKR1B1 has been detected in endometrium (Madore et al 2003) and also in IVF bovine embryos (Dode et al 2006, El-Sayed et al 2006 and is associated with failure to establish pregnancy and resorption (El-Sayed et al 2006).…”
Section: Development and Gene Expression In Parthenotesmentioning
confidence: 99%
“…AKR1B1 is also known as the cause for cell apoptosis in somatic cells that accumulate sorbitol (Galvez et al 2003, Wirtu et al 2004. Expression of AKR1B1 has been detected in endometrium (Madore et al 2003) and also in IVF bovine embryos (Dode et al 2006, El-Sayed et al 2006 and is associated with failure to establish pregnancy and resorption (El-Sayed et al 2006).…”
Section: Development and Gene Expression In Parthenotesmentioning
confidence: 99%
“…46,47 Activation of these pathways, in turn, is known to be associated with glucose-mediated apoptosis related to the development of microvascular complication of diabetes. [48][49][50][51] Recent studies have demonstrated Glucose, TGF-b and mesangial cell apoptosis T Khera et al that the pro-apoptotic effects of these pathways may each be mediated by increased generation of superoxide, as normalising mitochondrial superoxide production prevents glucose induced activation of protein kinase C, sorbitol accumulation of formation of advanced glycation end products in cultured endothelial cells. 52 This is also consistent with recent data suggesting that high glucose may promote mesangial cell apoptosis by oxidant-dependent mechanisms.…”
Section: Glucose Tgf-b and Mesangial Cell Apoptosis T Khera Et Almentioning
confidence: 99%
“…On the other hand, hyperglycemia also shifts the glucose glycolytic pathway into alternative pathways that are considered mediators of hyperglycemia induced cellular injury (26). The damage resulting from hyperglycemia includes elevation of advanced glycation end products (AGEs), hexosamine and polyol pathway, activation of beta 2 isoform PKC and alteration of myocardial structure and function (41)(42)(43)(44)(45)(46)(47). In addition, it has been suggested that hyperglycemia is linked to altering the expression and function of both the ryanodine receptor (RyR) and sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA), and this alteration may contribute to impair myocardial systolic and diastolic function (26).…”
Section: Hyperglycemiamentioning
confidence: 99%
“…Insulin resistance is more likely to create an abnormal environment, rather than causing another stressor (e.g., pressure/volume overload, metabolic inbalance, energy defect or decreased perfusion). Insulin resistance makes the heart unable to maintain homeostasis of its energy and function, which may favor the development of cardiomyopathy and heart failure (45,80,81). Fig.…”
Section: Dilated Cardiomyopathy and Heart Failurementioning
confidence: 99%